2021
DOI: 10.5653/cerm.2021.04819
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid therapy in assisted reproduction

Abstract: As glucocorticoids are well-known as important regulators of stress and the immune system, their function and clinical use have elicited substantial interest in the field of reproduction. In particular, the effect of glucocorticoid therapy on endometrial receptivity during assisted reproduction, including in vitro fertilization (IVF) cycles, has led to a great deal of interest and controversy. However, previous studies have not been able to provide consistent and reliable evidence due to their small, non-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…With regards to the safety of glucocorticoid administration, animalstudies have reported foetal growth retardation, cardiovascular, metabolic, neuroendocrine disorders, and teratogenic effects. In humans, increased risk of miscarriage, preterm births, gestational hypertension, and diabetes have been reported, even if the data are limited ( Kim, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regards to the safety of glucocorticoid administration, animalstudies have reported foetal growth retardation, cardiovascular, metabolic, neuroendocrine disorders, and teratogenic effects. In humans, increased risk of miscarriage, preterm births, gestational hypertension, and diabetes have been reported, even if the data are limited ( Kim, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, glucocorticoids are reported to affect local inflammation and immune response in the endometrium [ 37 ], potentially affecting embryo implantation. The use of glucocorticoids in assisted reproduction to improve the embryo implantation rate has been proposed, though controversial [ [38] , [39] , [40] ]. A Cochrane meta-analysis [ 41 ] of 13 randomized controlled trials (RCTs) found that glucocorticoid therapy led to no significant improvement in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women, fetal GC overexposure can also be caused exogenously by maternal treatment with synthetic GCs for a variety of clinical conditions such as congenital adrenal hyperplasia, rheumatoid arthritis, asthma, and other inflammatory conditions [ 30 ]. Synthetic GCs have also been given for immune suppression to women planning pregnancy either with transplanted organs or using in vitro fertilization (IVF) procedures, which leads to excess embryonic GC exposure from the earliest stages of development [ 31 , 32 ]. In addition, later in pregnancy, antenatal treatment with synthetic GCs is given routinely to women threatened with pre-term delivery to improve neonatal viability of their infants, although in 50% of cases delivery does not actually occur until much nearer to full term [ 30 ].…”
Section: Feto-placental Glucocorticoid Exposurementioning
confidence: 99%